2012
DOI: 10.1111/liv.12026
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐Wake profiles in patients with primary biliary cirrhosis

Abstract: Patients with PBC exhibited a delay in sleep timing that was associated with impaired sleep quality/quality of life. In addition, an interplay was observed between diurnal preference and the daytime course of pruritus/sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
(45 reference statements)
0
37
0
Order By: Relevance
“…The increase in melatonin serum levels (observed in Mdr2 2/2 mice) was likely caused by enhanced AANAT expression and melatonin secretion by cholangiocytes by a compensatory mechanism related to reduced AANAT expression in the pineal gland of Mdr2 2/2 mice. The latter is supported by studies demonstrating a disturbance in sleep-wake profiles in patients with PBC and in the hepatic circadian clock (both regulated by the pineal gland) in a mouse model of alcohol-induced hepatic steatosis (22,23). In Mdr2 2/2 mice exposed to prolonged dark, the increase in melatonin serum levels is probably caused by enhanced AANAT expression by pineal gland and melatonin secretion by the pineal gland (24); further studies are necessary to understand the decrease in melatonin secretion by cholangiocytes during prolonged dark exposure.…”
Section: Discussionmentioning
confidence: 82%
“…The increase in melatonin serum levels (observed in Mdr2 2/2 mice) was likely caused by enhanced AANAT expression and melatonin secretion by cholangiocytes by a compensatory mechanism related to reduced AANAT expression in the pineal gland of Mdr2 2/2 mice. The latter is supported by studies demonstrating a disturbance in sleep-wake profiles in patients with PBC and in the hepatic circadian clock (both regulated by the pineal gland) in a mouse model of alcohol-induced hepatic steatosis (22,23). In Mdr2 2/2 mice exposed to prolonged dark, the increase in melatonin serum levels is probably caused by enhanced AANAT expression by pineal gland and melatonin secretion by the pineal gland (24); further studies are necessary to understand the decrease in melatonin secretion by cholangiocytes during prolonged dark exposure.…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that circadian rhythm and melatonin synthesis is associated with the pathophysiology of cholangiopathies and liver cirrhosis. A previous study using 74 PBC patients, 60 cirrhosis patients, and 79 healthy individuals has found that sleep timing is significantly delayed in patients with PBC or cirrhosis, and delayed sleep timing is associated with impaired sleep quality in PBC patients . Another study using 13 PBC patients, seven cirrhosis patients, and six healthy individuals found that patients with PBC or cirrhosis had poor sleep quality assessed by the Pittsburgh Sleep Quality Index .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…Strikingly, these features were almost entirely absent from patients with low levels of fatigue. Different combinations of these associated features are seen in other CLD, with autonomic dysfunction the prominent association in PBC, and autonomic dysfunction and sleep disturbance the prominent associations in NASH …”
Section: Management Of Fatigue In Practicementioning
confidence: 99%